2014
DOI: 10.3944/aott.2014.14.0156
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of scaphotrapezial trapezoidal osteoarthritis with resection of the distal pole of the scaphoid

Abstract: Application of a pyrocarbon implant appears to be useful for pain relief and may help prevent secondary deformities in the treatment of scaphotrapezial trapezoidal arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 20 publications
4
13
0
Order By: Relevance
“…Several authors report satisfactory pain reduction (less than 2.5 on a 0-10 scale) after distal pole resection of the scaphoid. 8,12,14 In accordance with these studies, our patients reported an average pain score of 2.1 on a 0 to 10 scale. In general, STT arthrodesis also results in good pain relief, with only 5% of patients reporting mild postoperative pain.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Several authors report satisfactory pain reduction (less than 2.5 on a 0-10 scale) after distal pole resection of the scaphoid. 8,12,14 In accordance with these studies, our patients reported an average pain score of 2.1 on a 0 to 10 scale. In general, STT arthrodesis also results in good pain relief, with only 5% of patients reporting mild postoperative pain.…”
Section: Discussionsupporting
confidence: 87%
“…All studies reporting on distal pole resection of the scaphoid describe an increase of the radiolunate angle 5,8,12,13,16,17 postoperatively. In 3 studies, 8,16,14 this increase is reported to be statistically significant. Although patients do well on the short-term and midterm follow-up evaluations and the significance of these findings are unclear, they remain a cause of concern on the long term.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…17,18 The occurrence of a static or dynamic DISI pattern of carpal instability as a result of distal scaphoid resection has been reported in several studies. 15,16,19 Tendon interposition did not to affect the degree of DISI deformity. 16 Patients without fibrous interposition after distal scaphoid excision showed significantly greater wrist flexionextension motion than patients with soft-tissue interposition.…”
Section: Discussionmentioning
confidence: 80%
“…6 A Pyrocarbon implant to fill the gap may help to prevent carpal instability. 19 In this survey, implant arthroplasty was mainly performed in France. Compared with distal scaphoid excision, the main advantage of this procedure is that it retains scaphotrapezial mobility without destabilizing the carpal bones.…”
Section: Discussionmentioning
confidence: 99%